PENGARUH PEMBELAJARAN DARING TERHADAP HASIL BELAJAR MAKUL STATISTIK DESKRIPTIF PRODI PENDIDIKAN EKONOMI FKIP UNTAN - Sulasmi Sulasmi; Mashudi Mashudi; Husni Syahrudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study is entitled the effect of online learning on the learning outcomes of theDescriptive Statistics course for students of the Economic Education Study Program,FKIP Tanjungpura University and aims to determine whether there is an influenceand how much online learning has on the learning outcomes of the DescriptiveStatistics course in the students of the Economic Education Study Program, FKIPTanjungpura University. The research method used is a descriptive method in theform of research using influence studies. The source of population data is allstudents of the descriptive statistics course of the Economic Education StudyProgram-regular B, totaling 22 people. Data collection techniques used are indirectcommunication techniques, namely using a questionnaire. The results of dataanalysis in this study show a simple regression equation Y' = 96,692 + -0.311x,which means that if online learning is 0 (zero), then learning outcomes are positive,namely 96,692 and every decrease in online learning is worth 1, then learningmotivation will also decrease. of -0.311. The result of the coefficient of determinationis 0.192, which means that online learning has an effect of 19.2% on learningoutcomes and is included in the category of very low influence.Keywords: Online Learning, Learning Outcomes